Association between severity score, inflammatory levels and DNA damage in intensive care patients - Mattje, Andriela Vieceli; Molz, Patrícia; de Oliveira, Caio Fernando; Schlickmann, Diene da Silva; Renner, Jane Dagmar Pollo; Kraether Neto, Leo; Prá, Daniel; Franke, Silvia Isabel Rech (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and Objectives: The Intensive Care Unit (ICU) is responsible for the treatment of critical patients and monitoring it continuously can improve the quality of care provided. This study aims to associate the Simplified Acute Physiology Score (SAPS 3) with inflammatory levels and genomic damage in patients admitted to the ICU of a hospital in Vale do Taquari, Rio Grande do Sul, Brazil. Methods: This is a cross-sectional study conducted with 22 patients from an adult ICU,between January and June 2016. The SAPS 3 was scored by the medical staff at the admission of patients and blood samples were obtained after 24 and 72 hours of hospitalization for C-Reactive Protein (CRP) dosing and DNA damage. Results: The SAPS 3 score was not associated with 24-and 72-hours CRP. However, the SAPS 3 score was significantly associated with the index and frequency of DNA damage, only after 72 hours of hospitalization. Conclusion: The severity score was not associated with CRP levels, but with DNA damage only after 72 hours of admission. Critical Care. Simplified Acute Physiology Score. Polymerase Chain Reaction. DNA damage.